2010
DOI: 10.1002/anie.200905684
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Separable Nanocatalysts: Bridges between Homogeneous and Heterogeneous Catalysis

Abstract: Recovery and reuse of expensive catalysts after catalytic reactions are important factors for sustainable process management. The aim of this Review is to highlight the progress in the formation and catalytic applications of magnetic nanoparticles and magnetic nanocomposites. Directed functionalization of the surfaces of nanosized magnetic materials is an elegant way to bridge the gap between heterogeneous and homogeneous catalysis. The introduction of magnetic nanoparticles in a variety of solid matrices allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
600
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,377 publications
(604 citation statements)
references
References 440 publications
1
600
0
3
Order By: Relevance
“…Among all tested solvents (Table 3, Entries 1-7), water was found to be the best solvent in terms of the product yield (Table 3, Entry 7). Next, the effect of catalyst loading (3,5,6,7,8, and 10) on the model reaction was evaluated (Table 3, Entries 8-12). The results in Table 3 showed that the best results were obtained in 50 min in the presence of 5 mg of catalyst (Table 3, Entry 9).…”
Section: 3-dihydroquinazoline-4(1h)-onesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all tested solvents (Table 3, Entries 1-7), water was found to be the best solvent in terms of the product yield (Table 3, Entry 7). Next, the effect of catalyst loading (3,5,6,7,8, and 10) on the model reaction was evaluated (Table 3, Entries 8-12). The results in Table 3 showed that the best results were obtained in 50 min in the presence of 5 mg of catalyst (Table 3, Entry 9).…”
Section: 3-dihydroquinazoline-4(1h)-onesmentioning
confidence: 99%
“…[5,6] Therefore, the search for finding new support materials and heterogenization techniques is a hot research topic in modern research in catalysis. Among various solid supports used for the immobilization of metallic catalysts, magnetic nanoparticles have emerged as a robust and high-surface-area heterogeneous catalyst support, because they could not only stabilize the reaction catalytic species, but also improve the catalytic activity [7][8][9][10][11][12] The simple separation of MNPs-supported catalysts from products or mixture reaction by an external magnet is the most notable advantage of magnetic nanoparticles. [13][14][15] It is noteworthy that magnetic-supported catalysts can be reused many times while keeping their initial activity.…”
Section: Introductionmentioning
confidence: 99%
“…20 Magnetic separation using superparamagnetic nanoparticles and hybrid magnetic nanomaterials with organic or inorganic coatings, that can be modified with specific recognition groups, was first applied for cell sorting and separation of biologically active components, but later received attention in other fields of application, such as for heavy metal recovery [23][24][25] and catalyst separation. 26 Magnetic separation has several advantages in comparison with other traditional separation techniques as it avoids the use of solvents and other costly consumables, also avoiding mass loss, which is intrinsic to these techniques. Additionally, the target component can be isolated directly from crude samples such as blood, soil, food, or any other complex fluid, which greatly simplifies the separation process as it avoids laborious filtration or centrifugation steps, saving time and energy.…”
Section: Magnetic Separation: From Biotechnology To Catalysismentioning
confidence: 99%
“…26 The main role of the silica/polymer shell is to prevent any direct contact of the magnetic core with additional reagents to avoid unwanted interactions, such as acidic corrosion or oxidation. The presence of a silica layer facilitates the characterization of metal nanoparticle catalysts (see discussion bellow) and the control of metal dispersion by the means of surface modification with organic functional groups.…”
Section: Going Beyond Silicamentioning
confidence: 99%
“…The magnetic nanoparticles anchored on solid support serve as heterogenous catalyst allowing facile separation of catalyst from reaction products. 23 Superparamagnetic copper ferrite-graphene nanocomposite prepared via hydrothermal method acts as excellent catalyst for the reduction of nitroarenes. The big advantage of the catalyst is that it can be easily recovered and retains the catalytic activity even after five catalytic cycles.…”
Section: Introductionmentioning
confidence: 99%